1994
DOI: 10.1111/j.1348-0421.1994.tb01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Host‐Associated Treponeme Proteins to Collagens and Laminin: A Possible Mechanism of Spirochetal Adherence to Host Tissues

Abstract: The polypeptides of seven strains of human treponemes were investigated by immunoblot analysis for their binding to the human placental collagens and laminin. Of the treponemal polypeptides, eleven polypeptides, 45‐kDa, 49‐kDa, and 62‐kDa polypeptides from T. pallidum ATCC 27087, a 48‐kDa polypeptide from T. phagedenis biotype Reiter, 51‐kDa and 53‐kDa polypeptides from T. vincentii ATCC 35580, 30‐kDa, 53‐kDa and 63‐kDa polypeptides from T. socranskii subsp. buccale ATCC 35534, a 52‐kDa polypeptide from T. den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 38 publications
(35 reference statements)
0
41
2
Order By: Relevance
“…In order to obtain a pure culture, the procedure was repeated more than 10 times, and spirochetal colonies were picked from solid sterility test medium supplemented with horse serum (35). Later, TYGVS medium was used as the routine culture medium and an anaerobic chamber (85% N,, 10% H,, 5% COz) was used for anaerobic conditions (34,36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain a pure culture, the procedure was repeated more than 10 times, and spirochetal colonies were picked from solid sterility test medium supplemented with horse serum (35). Later, TYGVS medium was used as the routine culture medium and an anaerobic chamber (85% N,, 10% H,, 5% COz) was used for anaerobic conditions (34,36).…”
Section: Methodsmentioning
confidence: 99%
“…After electrophoresis, the gel was stained with Coomassie brilliant blue R-250 or used for Western transfer. Western transfer of the antigens from the gel to a nitrocellulose membrane was performed as described previously (19,34). An immunoblotting analysis was carried out by using goat anti-rabbit immunoglobulin G conjugated with peroxidase as the second antibody as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…The adherence of human oral spirochetes to host tissues has been reported (21,23). T. socranskii possesses collagen-and laminin-binding polypeptides (23). In this study, T. socranskii was detected more often in subgingival plaque samples than in saliva samples.…”
Section: Periodontitismentioning
confidence: 58%
“…Therefore, further study will be necessary to make clear the relationship between the presence of T. socranskii in health-associated plaque and risk for periodontitis . The adherence of human oral spirochetes to host tissues has been reported (21,23). T. socranskii possesses collagen-and laminin-binding polypeptides (23).…”
Section: Periodontitismentioning
confidence: 99%
“…Fenno et al (17) also found that recombinant Msp did not show an oligomeric form but it adhered to fibronectin and laminin. Umemoto et al (84,86) reported that T vincentii and T socranskii subsp. huecale have outer envelope proteins that bind to laminin, and that the 95 kDa outer sheath protein of T medium binds to type IV collagen.…”
Section: Adherencementioning
confidence: 99%